CARAPACE WIDTH-BODY WEIGHT RELATIONSHIP AND CONDITION FACTORS OF Portunus sanguinolentus IN SOUTHEASTERN BONE GULF, SOUTHEAST SULAWESI - Abdul Hamid; Syamsul Kamri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2026)
This study aimed to determine the body size, carapace width-weight relationship, and condition factors of Portunus sanguinolentus in southeastern Bone Gulf, Southeast Sulawesi. Samples of P. sanguinolentus were obtained from crab fishermen and were collected monthly. The measured data consisted of carapace width and body weight, stratified by sex. The Mann-Whitney test was used to assess differences in body size between males and females. The carapace width-body weight relationship was analyzed using nonlinear and linear regression analysis, and a t-test was performed on the value of b = 3 to determine the growth pattern of the crab. The condition factor analyzed was the relative condition factor. The results showed that male P. sanguinolentus had a larger body size than females. The carapace width-body weight relationship of male, female, and pooled P. sanguinolentus showed a strong and positive correlation, and the growth pattern was negative allometric. The relative condition factor of males was higher than that of females. The results of this study can be used as a basis for managing P. sanguinolentus in the southeastern Bone Gulf.